Eclectic continuum, distinct discipline or sub-domain of communication studies? Theoretical considerations and empirical findings on the disciplinarity, multidisciplinarity and transdisciplinarity of journalism studies - Löffelholz, Martin; Rothenberger, Liane (Brazilian journalism research, 2011)
Is journalism studies a sub-domain of communication studies, adistinct discipline, a multidisciplinary merger or a transdisciplinary endeavour? This question is discussed by analyzing the 2008 and2009 volumes of seven academic journals focusing on journalismresearch. The sample includes 349 articles published in BrazilianJournalism Research, Ecquid Novi, Journalism & CommunicationMonographs, Journalism & Mass Communication Quarterly, PacificJournalism Review, Journalism Studies, or Journalism: Theory,Practice and Criticism. Overall, the findings reveal that journalismresearch mainly applies theoretical approaches and empiricalmethods deriving from other disciplines, particularly sociology, psychology or cultural studies. In many countries, however, journalism studies has reached a comparatively high level of institutionalization indicated by the large number of specific schools, professorships, professional associations and respective academic journals. In conclusion, we argue that journalism studies is a sub-domain of communication studies, which integrates andtranscends various disciplines aiming to become one of the axialsubjects of the 21st century.